Public Administration in an Information Age - A Handbook - W.B.H.J. van de Donk (ed.) (Informatization Developments and the Public Sector, 1998)
"This book is a joint effort of researchers who have been involved in research-projects and programmes that have been trying to chart and reflect upon the implications of Information and Communication Technologies (ICTs) for Public Administration. Since the 1950s, computers had largely facilitated and the transformation of the minimal 'Night-Watch-state' into the modern 'Welfare-state', through their contribution to their effectivity, productivity and efficiency. In most Handbooks of Public Administration, computers are seen as neutral instruments and, most of the time, the role of computer technologies in the transformation of public administration is completely neglected. This 'deafening silence' is a great contrast with the way ICT's are actually changing public administration. The faster the developments in a field of study are, the more difficult it is to let the theories, related to that field of study, mature. In such circumstances, most statements will remain provisional and context-dependent. 25 years of research in Irvine (California) and Kassel (Germany) and more than 10 years of research in Tilburg/Rotterdam (The Netherlands) and about seven years of research in Glasgow/Nottingham (the United Kingdom) nonetheless enables the presentation of a modest image of public administration as it is entering the information age. Researchers in each of these groups have, nevertheless, not stopped trying to phrase theories about the implications of informatization for public administration with a more or less larges scope, that are robust in different contexts and over longer periods of time. These results and theories, covering a broad set of elements of the body of knowledge of public administration, are presented in this volume. As the authors try to demonstrate in this book, informatization developments in public administration do not only challenge the existing body of knowledge of the public administration discipline, but they are also opening up new perspectives and paradigms for the study of public administration."